Smart Nutrition for a Golden Generation: Nutrition Education for Mothers of Toddlers - Br Ginting Munthe, Novita; Sembiring, Iskandar Markus; Ginting, Nurtiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Optimal nutrition during early childhood is crucial in supporting the overall growth and development of children. This period is known as the golden age, during which brain and physical development occur very rapidly. Therefore, nutrition education for mothers of young children is a vital step in ensuring that future generations grow up to be healthy and intelligent individuals. Knowledge about the nutritional needs of young children, the proper way to provide complementary feeding (MP-ASI), and the prevention of malnutrition are the main focuses of this education. This article also presents various essential nutrients needed by young children and practical tips for mothers in providing MP-ASI. The Community Service Program (PKM) was held at the Nurtiana Ginting Clinic, Serdang Bedagai Regency, on May 4, 2024, involving 18 participants. The primary goal of this PKM is that with good nutrition education, it is hoped that mothers will become more skilled in providing healthy and balanced meals, thus supporting the creation of a healthy and intelligent golden generation. Adequate knowledge will help mothers make the right decisions regarding diet and food choices, ultimately supporting the creation of a healthy, intelligent, and highly competitive golden generation. Nutrition education also plays an important role in preventing various health problems that can arise from nutritional deficiencies or excesses, thereby significantly improving children's quality of life.